2022
DOI: 10.1371/journal.pone.0263001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on scientific research in the life sciences

Abstract: The COVID-19 outbreak has posed an unprecedented challenge to humanity and science. On the one side, public and private incentives have been put in place to promptly allocate resources toward research areas strictly related to the COVID-19 emergency. However, research in many fields not directly related to the pandemic has been displaced. In this paper, we assess the impact of COVID-19 on world scientific production in the life sciences and find indications that the usage of medical subject headings (MeSH) has… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(81 citation statements)
references
References 17 publications
4
53
0
1
Order By: Relevance
“…It is certainly worth investigating what trends will emerge during the 2020s. Nonetheless, we may have to wait until half of the present decade has passed before understanding if there is indeed a decrease in the yielding of NMNPIs, as data from 2020-2022 could be biased due to the limitations imposed by the COVID-19 pandemic; a caveat already acknowledged in other research fields [18].…”
Section: Discussionmentioning
confidence: 99%
“…It is certainly worth investigating what trends will emerge during the 2020s. Nonetheless, we may have to wait until half of the present decade has passed before understanding if there is indeed a decrease in the yielding of NMNPIs, as data from 2020-2022 could be biased due to the limitations imposed by the COVID-19 pandemic; a caveat already acknowledged in other research fields [18].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, multidisciplinary scientific research contributed enormously to the rapid identification of drugs and vaccines, as well as providing evidence about the mechanisms of action of the virus and consequently also of the effectiveness of containment measures. Basic research, clinical trials and epidemiological studies have helped to expand knowledge about COVID-19 with unprecedented rapidity ( 52 – 54 ). However, in some cases policymakers, discouraged from making unpopular decisions, have ignored scientific evidence, with devastating effects in their countries ( 55 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Raynaud et al showed a rise in COVID-19 related publications and a decrease in the proportion of non-COVID-19 publications in high-impact medical journals [ 10 ]. Riccaboni and Verginer analyzed the impacts of COVID-19 on research in the PubMed database and found the COVID-19 pandemic induced a sudden surge in COVID-19 related publications [ 11 ]. In contrast, non-COVID-19 research areas experienced a remarkable reduction in overall publishing rates and funding [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Riccaboni and Verginer analyzed the impacts of COVID-19 on research in the PubMed database and found the COVID-19 pandemic induced a sudden surge in COVID-19 related publications [ 11 ]. In contrast, non-COVID-19 research areas experienced a remarkable reduction in overall publishing rates and funding [ 11 ].…”
Section: Introductionmentioning
confidence: 99%